An investigation into strain within the patellar tendon - Campbell, Katherine Gillian (2011)
Tendon injuries have, for many years, frustrated clinicians and patients alike due to their longevity and resistance to therapy. In recent years there has been good response in the extensor tendons of the lower limb to an intense painful eccentric exercise protocol. As yet there is no established reason known why a tendon should develop degeneration within its structure or why it should respond to the eccentric exercises. We do however know that, like bone, tendons are biologically active and rapidly adapt to the mechanical environment to which they are exposed. Recent investigations have revealed that within a tendon such as the Achilles or the patellar tendon there may be regions that experience different strains to the rest of the tendon. Much of this work has been in vitro and an ultimate goal would be the development of a non-invasive method by which intra-tendinous strain might be measured.